2000
DOI: 10.1580/1080-6032(2000)011[0257:pfaaem]2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Planning for an annual episodic mass gathering: emergency department and clinic utilization in Yellowstone

Abstract: Utilization analysis revealed differences between conventional mass gatherings and the mass gatherings in Yellowstone. Because of the unique conditions and populations found in a wilderness area, conventional mass gathering emergency medical service models may not be an appropriate model for planning health care in a national park. Analysis of utilization data can help plan resources for emergency and primary health care for a park population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…5 The comparable rate of injury for the current study is 0.3/ 1000 PD. A study reported the services rendered in 1995 by the emergency department at Yellowstone Park indicated that recreational visitors needed care in their clinic for more injuries and illnesses than park staff, 6 a finding that is consistent with the observation in the current study as well. Information about evacuations was also included both in the NOLS report and in a report from the 1985 Scout Jamboree.…”
Section: Discussionsupporting
confidence: 89%
“…5 The comparable rate of injury for the current study is 0.3/ 1000 PD. A study reported the services rendered in 1995 by the emergency department at Yellowstone Park indicated that recreational visitors needed care in their clinic for more injuries and illnesses than park staff, 6 a finding that is consistent with the observation in the current study as well. Information about evacuations was also included both in the NOLS report and in a report from the 1985 Scout Jamboree.…”
Section: Discussionsupporting
confidence: 89%
“…The drug expenses incurred during the event were mostly from analgesics and antibiotics. A study by Chang et al [13] shows findings similar to those of this study. These medications are a suitable treatment for the common ailments experienced by the masses walking to Karbala.…”
Section: Discussionsupporting
confidence: 92%
“…The journey to Karbala requires several days of walking, resulting in musculoskeletal pain and injuries, which explain the high cost of analgesics, used to control muscular pain, in addition to antibiotics, used treat infection related to injury and respiratory infections. A study by Chang et al shows findings similar to this study [13].…”
Section: Discussionsupporting
confidence: 91%